2019–2020 Florida Citrus Production Guide: Weeds - Stephen H. Futch; Brent A. Sellers; Ramdas G. Kanissery (EDIS)
Weed management in Florida citrus is an important component of any successful integrated pest management (IPM) program. IPM programs utilize a combination of control practices including but not limited to cultural, preventive, mechanical, chemical, or biological methods. Weed management is expensive and a major component of the total citrus production program. Time spent developing this production program can provide significant economic and environmental returns. The goal of weed management is to minimize the competitive effect of weeds on the citrus tree, be it young or mature. An understanding of the growth and competitive nature of the weed is important. The objective of today's weed management program is to suppress and control weeds so that they do not cause damage to the tree, impact yield, or impede grove and harvesting operations. Complete and total elimination of all weeds from the grove floor is neither necessary nor warranted.